Exploring the Role of Homeopathy in Immunomodulation in the Context of Air Pollution Induced Cough (Homoeopathy for All, 2024)
The present air pollution levels in  Delhi have escalated to a hazardous  extent, surpassing the 400 Air  Quality Index (AQI) threshold.  Given the prevailing air quality  crisis in most metro cities, it is  crucial to examine the possible  consequences on respiratory well being, specifically in regard to the  occurrence of persistent coughing.  The primary cause of the current low  air quality may be largely attributable  to a combination of causes, which  include emissions from vehicles,  pollutants released by industries, and  the burning of agricultural waste.  The presence of harmful substances,  including particulate matter (PM2.5  and PM10) and gases such as  nitrogen dioxide (NO2) and sulphur  dioxide (SO2), presents a substantial  risk to the respiratory system,  potentially leading to compromised  lung function. Moreover, previous  research has demonstrated a strong  association between elevated  concentrations of atmospheric  pollutants and an augmented  susceptibility to respiratory ailments,  such as persistent cough1.  Acknowledging the crucial  significance of environmental  elements, namely air quality, is of  utmost importance when devising  approaches for management or  prophylaxis against cough, as they  play an essential role in the control  and prevention of respiratory  conditions. The intricate relationship  between immunity and cough serves  as a fundamental aspect of our body's  defense mechanism against various  respiratory challenges, including  those posed by air pollution.2,3 Homeopathy, through the practice of  immunomodulation, offers a holistic  approach to enhancing the body's  immune response. By promoting  immunomodulation, homeopathic  treatments aim to strengthen the  immune system's ability to adapt  and respond effectively to different  respiratory irritants, thereby  alleviating cough symptoms and  contributing to overall respiratory  health. This synergy between  immunity and homeopathy  highlights the potential of  homeopathic remedies in addressing  cough-related issues aggravated by  environmental factors such as air  pollution. This article delves into  homeopathic immunomodulation  for cough prophylaxis, exploring its  potential.
Keywords: hazardous; prophylaxis; pollution